Denmark : Stress Testing the Banking, Insurance, and Pension Sectors: Technical Note. (IMF Staff Country Reports; Country Report ;, 2014)
This Technical Note on Stress Testing the Banking, Insurance, and Pension Sectors on Denmark discusses that since the beginning of the global financial crisis, Danish banks have substantially increased their capital buffers. The banks' capital buffers provide for substantial loss absorbing capacity in case macro-financial conditions deteriorate. Under the most severe stress scenario, the aggregate Tier 1 ratio of large Danish banks drops by almost 4 percentage points, but the solvency position would remain adequate even in such a downturn scenario-underlining the value of solid capital buffers. Under the restrictive assumptions of the stress test, the adverse scenarios have large negative effects on the solvency and profitability of life insurance companies. Nonlife insurers would see a small decline in solvency ratios in the first year of the stress test. Though starting from lower solvency levels than life insurers, the aggregated impact on solvency ratios in the adverse scenario is comparably smaller.